Eyes to the West: Latin America and the Caribbean in the sights of Germany and the EU - Günther Maihold; Claudia Zilla (Stiftung Wissenschaft und Politik (SWP), 2023)
Europe is committed to revitalising its relations with Latin America and the Caribbean. This is evidenced by the numerous high-level visits from Germany and the EU to Latin American countries since the beginning of the year. In early June, the European Commission presented a "new agenda" for exchange with the region, and last month the German Bundestag's SPD parliamentary group released a position paper on the ways and reasons to strengthen the partnership. Slated to take place in July, the upcoming summit between the EU and the Community of Latin American and Caribbean States (CELAC) is expected to give new impetus to bi-regional relations. However, in order for such expressions of interest to be translated into a substantive reboot of the relationship, jointly developed initiatives will be needed. Such endeavours will need to account for and address changes in the triangular relationship between democracy, sustainable development and global governance.
Keywords: 320; Europe; EU; Latin America; Caribbean; CELAC; LAC; Mercosur; preservation of democracy; sustainable development; global governance